ANALISIS PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN OPERATOR PADA PT GIKEN PRECISION INDONESIA - Rusda Irawati; Dini Arimbi Carollina (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract: The purpose of this research is to know and analyze the extent of internal workload influence on operator employee performance in PT.Giken Precision Indonesia,  to  know  and  analyze  the  extent  of  the  effect  of  external  workload on operator employee performance in PT.Giken Precision Indonesia and to know and Analyze the extent of simultaneous influence between internal and external workload on employee performance of operator in PT. Giken Precision Indonesia. Data were obtained from 71 respondents in Moulding Department by conducting interviews and distributing  questionnaires,  multiple  linear  regression  test  was  used  to  know respondent attitude toward work load variable and employee performance. The result of the research shows that there is influence between work load to employee performance, that is, internal work load has positive effect on employee performance, while the external work load has negative effect on employee performance. Keywords: internal workload, external workload, and employee performance.